2019
DOI: 10.17645/mac.v7i3.1910
|View full text |Cite
|
Sign up to set email alerts
|

Newsworthiness and the Public’s Response in Russian Social Media: A Comparison of State and Private News Organizations

Abstract: Social media have become one of the most important news delivery channels due to their interactivity and large audiences. The content published by news organizations on social networking sites is of particular value to sociologists, because it allows measurement of users’ attitude to certain events. However, we understand that the media choose which events become news in accordance with certain criteria, such as news values. In this study, we decided to examine how news values determine the public’s response a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Yet, it is important to understand that these different components of engagement have different affordances and can serve different functions (e.g., Ferrer-Conill et al, 2021;Savolainen et al, 2020). Also empirically, it has been shown that the number of, for instance, shares, likes, and comments of political content is not influenced in the same way by the same predictors (e.g., Judina & Platonov, 2019;Larsson, 2018;Trilling et al, 2017). In the particular, liking political content has often been criticised as a means of engagement that takes so little effort that it hardly qualifies as a 'real' political action, as opposed to, for instance, writing a comment, which can require quite some cognitive resources and can lead to a meaningful exchange of opinions (see, e.g., Larsson, 2018).…”
mentioning
confidence: 99%
“…Yet, it is important to understand that these different components of engagement have different affordances and can serve different functions (e.g., Ferrer-Conill et al, 2021;Savolainen et al, 2020). Also empirically, it has been shown that the number of, for instance, shares, likes, and comments of political content is not influenced in the same way by the same predictors (e.g., Judina & Platonov, 2019;Larsson, 2018;Trilling et al, 2017). In the particular, liking political content has often been criticised as a means of engagement that takes so little effort that it hardly qualifies as a 'real' political action, as opposed to, for instance, writing a comment, which can require quite some cognitive resources and can lead to a meaningful exchange of opinions (see, e.g., Larsson, 2018).…”
mentioning
confidence: 99%
“…Use-case studies: While these news values are particularly defined for news stories from media channels, they also apply to social media news stories shared across platforms such as Facebook (Bednarek, 2016 ). Some other works consequently apply news value theory to news articles shared on Facebook (Park and Kaye, 2021 ), Twitter (Araujo and van der Meer, 2020 ) and the Russian social media site Vkontakte (Judina and Platonov, 2019 ). Park and Kaye ( 2021 ) studied the correlation between news values of social significance and deviance with social media users' tendency to like, comment and share mainstream news stories on Facebook.…”
Section: Related Work and Backgroundmentioning
confidence: 99%
“…As Caple and Bednarek (2015) suggest, semantic analysis may help understand the “overlap or mismatch” between news values promoted by news organizations and what the audience perceive as worth reading and responding to. Judina and Platonov’s (2019) investigation on users’ behaviour of likes, reposts and comments shows that a detailed classification of news values such as the DNVA model “seems reasonable” to determine readers’ response (p. 164). Venuti and Fruttaldo’s (2019) corpus analysis of news values constructed in news articles and Facebook users’ responses shows that readers react more to the event than to the news story.…”
Section: News Value and Readers’ Responsementioning
confidence: 99%